2020
DOI: 10.1111/ddg.14019
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of combined nevi and melanomas: Case‐control study with comparative analysis of dermoscopic features

Abstract: Background and objectives: Combined nevi (CN) show two or more components of major nevus subtypes and simulate melanomas. We investigated a panel of dermoscopic features and three dermoscopic algorithms for differentiating CN from melanomas.Patients and methods: Retrospective, blinded case-control study using dermoscopic images of 36 CN and 36 melanoma controls. Twenty-one dermoscopic features validated for the diagnosis of melanocytic lesions, the number of colors, and three dermoscopic algorithms were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
(52 reference statements)
1
13
0
5
Order By: Relevance
“…Because we had incomplete information on whether dermatoscopy images were taken in polarized or non‐polarized mode, we could not further analyse this potentially confounding factor. Our observations are in line with smaller case series 3,6,16,17 and with the results of a recent study by Schweizer et al ., 10 in which the authors reported a relatively low frequency of melanoma clues in CBN.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Because we had incomplete information on whether dermatoscopy images were taken in polarized or non‐polarized mode, we could not further analyse this potentially confounding factor. Our observations are in line with smaller case series 3,6,16,17 and with the results of a recent study by Schweizer et al ., 10 in which the authors reported a relatively low frequency of melanoma clues in CBN.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we demonstrate that this structureless blue area of CBN is typically well defined and often, albeit not always, located in the centre of the lesion. In these typical cases, the overall presentation of the CBN will be symmetrical with regard to colour and structure and not chaotic 10,16 . This presentation is also known as the targetoid combined blue naevus type 16 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Reed nevus, cellular blue nevus, deep penetrating nevus, and combined nevus are examples of truly benign lesions that nevertheless bear strong resemblance to melanoma, histologically as well, and may therefore result in overdiagnosis [36]. Even though the features expected to be exclusive to melanomas or nevi are described in increasingly specific terms, thus improving the correct clinical diagnosis [37], differentiation in these cases remains challenging.…”
Section: Underdiagnosis and Overdiagnosismentioning
confidence: 99%
“…Beispiele für eindeutig gutartige Läsionen, die aber selbst auf feingeweblicher Ebene Melanomen sehr stark ähneln und so zu Überdiagnosen führen können, sind der Reed Nävus, der zelluläre blaue Nävus, der deep penetrating nevus oder der kombinierte Nävus [36]. Auch wenn die Merkmale, die ausschließlich bei Melanomen oder bei Nävi zu erwarten sind, immer differenzierter beschrieben werden und die korrekte klinische Diagnose verbessern [37], bleibt die Unterscheidung in diesen Fällen schwierig.…”
Section: Unterdiagnosen Und üBerdiagnosenunclassified